"Social consensus and incomes policy": a comment - Tansey, Paul (Economic & Social Studies, 1992)
Most people are conditioned to believe that centralised pay deals are a good thing. They have names that stress harmony and consensus from National Understandings to Programmes for Economic and Social Progress. They are concluded not by mere interest groups but by "social partners". Their finalisation generates a strong "feelgood factor" as the drama of brinkmanship negotiations crystallises into a happy ending where everybody receives a payoff. This is reinforced strongly by the signatories to such agreements who, in the nature of things, will canvass the specific benefits of the resulting deal to their particular constituencies.
Keywords: Social consensus; Incomes policy; Ireland; Centralised bargaining